The apprehensive violence of death stranding: meditations on ropes and sticks - Steinmetz, Kevin F. (Video games, crime and control, 2024)
Hideo Kojima’s Death Stranding (2019) has an uneasy relationship with violence. Such destructive acts are often eagerly embraced by video games of almost all genres - from the banal bashing of cartoon enemies to the gory mutilation of on-screen foes. While violence is an option available to players navigating Kojima’s dystopian landscape, the game often discourages violent means through the careful structuring of game mechanics, imagery, and narratives. Players who attempt to use violence more than necessary will likely find the game unfulfilling - an outcome that appears to be a design choice. Instead, players are to revel in the subtle joy of trekking through the scenic landscapes, delivering packages to the grateful denizens of post-apocalypse America, and rebuilding a nation, one shelter at a time. This analysis considers Kojima’s use of violence in Death Stranding as a conflicted meditation on video game violence, providing a lens for understanding our cultural sensibilities toward violence.